BERBAGAI FAKTOR PENENTU PENYESUAIAN PSIKOLOGIS POSITIF PENYINTAS BENCANA PASCA BENCANA - Kartika Nurfathiyah (Paradigma, 2013)
Post-disaster disaster survivors experience severe obstacles in his adjustment. Nevertheless, natural disaster or trauma encountered in life is not entirely negative effect. Exposure below attempts to lay out the findings of research that actually proves that disaster survivors to be very powerful, very strong and can develop post-disaster. Factors that determine so helpless disaster after disaster survivors include social support, personal reinforcement in the form of self-acceptance, self-management, and positive coping strategies which can all be sourced from local cultural values.